End-user centred infrastructure operation: towards integrated end-use service delivery. (20th September 2016) - Knoeri, Christof; Steinberger, Julia K.; Roelich, Katy
Abstract: Reliable provision of water, energy and transportation, all supplied through infrastructure, is necessary for the most basic human and economic development to occur. Such development however, is not enabled by specific end-use products (e.g. litres of water, kWh of electricity, litres of diesel and petrol), or by infrastructure itself (i.e. the systems of energy, transport, digital information, water, waste and flood protection assets), but rather through the infrastructure end-use services (e.g. hygiene, thermal comfort, communication, or accessibility). The present form of infrastructure operation consists of supply systems provisioning unconstrained demand of end-use products, with larger consumption volumes corresponding to higher economic revenue. Providing infrastructure capacity to meet unmanaged growing demand is ultimately unsustainable, both in environmental and economic terms. Past research has focused on physical infrastructure assets on the one hand, and sustainable consumption and production on the other, often neglecting infrastructure end-use services. An important priority for sustainable infrastructure operation is therefore to analyse the infrastructure end-use service demands, and the variety of end-users' wants and behaviours. This paper outlines the key aspects of an end-user and service-centred approach to infrastructure operation. It starts with an overview of relevant research areas and literature. It then describes the infrastructure end-use services provided by different infrastructure streams quantitatively, with the UK domestic sector as an illustration. Subsequently, insights into infrastructure integration at the end-user level are presented. Finally, the infrastructure end-use service perspective is described as a holistic framework for intervention: understanding technological changes in context, acting directly on end-use demand, and including social implications of service-based solutions. Highlights: Infrastructure operation based on ever growing demand is unsustainable. Sustainable infrastructure operation requires the integration of end-users. End-users select active and passive technologies and define end-use demand levels. Providing infrastructure end-use services instead of products incentivises efficiency. Infrastructure end-use services and interrelation at the end-user level are analysed.